ANALISIS TINDAK TUTUR PERLOKUSI PADA FILM SEJUTA SAYANG UNTUKNYA KARYA HERWIN NOVIANTO SEBAGAI PEMANFAATAN BAHAN AJAR TEKS ULASAN DI SMA - Rifa Nurjanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Humans use language to give and receive information through various types of media, including audio and visual media. In speech events, sentences show the intent and purpose of communicating. The words spoken by a speaker can indicate the intent of the speaker or speakers so that other people can understand them more easily. In every communication process, speech events and speech acts occur. Speech acts are strongly influenced by the context or speech situation. This is due to the fact that the speaker and the interlocutor are talking about the same topic, at a certain time, place and situation, so that both of them can understand well the intended meaning of the conversation. In a situation where someone is speaking, their language skills greatly influence what they are saying. One of the main problems that often occur in communication is the difficulty of expressing the information to be communicated. The term "speech act" or "speech act" is used in pragmatics when speaking and communicating which refers to pragmatics. Speech acts with communicative language are intended so that listeners can understand what is conveyed by speakers. The circumstances surrounding the speech environment help speakers and listeners. In order to avoid misunderstandings about speech, it is very important to study the forms of perlocutionary speech acts. The discussion of this research plan is how to analyze perlocutionary speech acts. The aim of the research is to provide knowledge to the reader about the events of perlocutionary speech acts in the film "Sejuta Sayang Untuknya" by Herwin Novianto. This research uses a qualitative descriptive approach to collect literary sources and then conducts research directly into the field by seeing and talking to informants. This ensures that the data collected by the researcher is objective.